Establishing Cell Lines from Fresh or Cryopreserved Tissue from the Great Crested Newt (Triturus cristatus): A Preliminary Protocol - Strand, Julie (Animals (Basel), 2021)
SIMPLE SUMMARY: This research describes a successful protocol for establishing viable cell lines from one of the amphibian species that are severely threatened with extinction. For the study, fresh or cryopreserved tissue samples were used, and various parameters affecting the optimal growth conditions were tested, such as use of different media, impact of media change and the influence of contamination. We concluded that: (i) Using fresh tissue was more successful in terms of establishing cell lines; (ii) No differences were found between the media used for fresh tissue, while one medium had a positive effect on growth when using cryopreserved tissue; (iii) Contamination caused the tissue cultured to be destroyed; and (iv) Real-time cell analysis visualized a significant impact on cell growth pattern when media change was combined with PBS washing. This research demonstrated the potential of and the challenges to establishing amphibian cell lines, which provide an opportunity for implementing modern reproductive technologies as a future part of conservation strategies for endangered and threatened amphibian species. ABSTRACT: This study describes a successful protocol for establishing cell lines from the threatened Triturus cristatus in terms of collection, preparing, establishing, cryopreserving, thawing and quality checking. Different parameters such as media, media change, fresh vs. cryopreserved tissue and seeding density were tested to optimize culture conditions for this species. With fresh tissue, no considerable differences in the use of two different media were found, but with cryopreserved tissue, a combination of ITS (insulin/transferrin/selenite) and 2-mercaptoethanol had a positive effect on growth. Real-time measurements on the cell lines were used, for the first time in amphibian cells, to investigate the effect of different treatments such as media change with or without washing. Media change had a positive impact on the cells, whereas the effect was negative when combined with washing. It is concluded that establishment of cell lines is possible from the great crested newt, especially when using fresh tissue, but much more challenging if the tissue has been cryopreserved. Real-time measurement during cell culture is a useful tool to visualize the sensitivity of amphibian cells during different culture treatments.